The Crisis and Beyond - Henning Klodt; Harmen Lehment (Kiel Institute for the World Economy (IfW), 2009)
We are looking back to one of the most severe financial crises ever. The subprime crisis, as future generations may call it, was not just a crisis among others, but had a truly global dimension. There are still doubts whether the flames are really out, but in any case the recent crisis has far-reaching implications for all areas of Weltwirtschaft, including monetary and fiscal policy, the nature of global trade and capital flows, environmental policy, competition for natural resources, economic development, the welfare state, and much more. Many dangers loom, from new forms of protectionism, to threats to the environment and development aid, to new social divides. Even after the crisis, it is very unlikely that we will return to business as usual; the world will presumably move to a new financial architecture, new political and trade relations, new forms of global interconnectedness. The crisis has been recognized as a major challenge not only for the world economy, but also for economic research and economic policy advice. Over the past months, economists working at or visiting the Kiel Institute have prepared a number of essays on several aspects of the crisis and on its potential long-term consequences. These essays are now collected in this e-book in a condensed and easily accessible manner. The editors and authors hope that the book will initiate a lively debate among researchers and policy makers who share a common interest in preventing another such crisis to occur in the future.
Keywords: 330; Finanzmarktkrise; Wirtschaftspolitik; Welt